Die Beziehungen zwischen dem Karpatenbecken und dem Mediterraneum von der II. Hälfte des 6. bis zum 8. Jahrhundert n. Chr. anhand Schmuckstücken und Kleidungszubehör - Blay, Adrienn Katalin (Dissertationes Archaeologicae, 2021)
Abstract of PhD thesis submitted in 2020 to the Archaeology Doctoral Programme, Doctoral School of History, Eötvös Loránd University under the supervision of Tivadar Vida, Budapest and to the Institute of the Prehistory and Medieval Archaeology at the Albert-Ludwigs-University of Freiburg (Breisgau) under the supervision of Sebastian Brather.